2001
DOI: 10.1002/micr.1007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of vascularized nerve graft: Evaluation of nerve regeneration using choline acetyltransferase activity

Abstract: A comparative study of nerve regeneration was performed on vascularized nerve graft (VNG) and free nerve graft (FNG) in Fischer strain rats. A segment of the sciatic nerve with vascular pedicle of the femoral artery and vein was harvested from syngeneic donor rat for the VNG group and the sciatic nerve in the same length without vascular pedicle was harvested for the FNG group. They were transplanted to a nerve defect in the sciatic nerve of syngeneic recipient rats. At 2, 4, 6, 8, 12, 16, and 24 weeks after o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…[7][8][9][10][11] In our study the functional recovery was significantly better in the VNG than in NNG group in early assessments; on the contrary, in long-term assessments the difference of the regeneration was almost 5%. A significant increase in vessels and regenerated axons was observed in VNG after 30 days; on the other hand, although after 90 days the mean numerical values of axonal counting and morphometric nerve study were slightly better in the VNG, the differences between the two grafted groups were not statistically significant (p > 0,05).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…[7][8][9][10][11] In our study the functional recovery was significantly better in the VNG than in NNG group in early assessments; on the contrary, in long-term assessments the difference of the regeneration was almost 5%. A significant increase in vessels and regenerated axons was observed in VNG after 30 days; on the other hand, although after 90 days the mean numerical values of axonal counting and morphometric nerve study were slightly better in the VNG, the differences between the two grafted groups were not statistically significant (p > 0,05).…”
Section: Discussioncontrasting
confidence: 55%
“…Other histomorphological and morphometric studies [5][6][7] showed the morphologically optimal regeneration using VNG because of the immediate restoration of the circulation. On the contrary, Iwai et al 8 , found a better regeneration in the VNG than in NNG group at four weeks postoperatively, but they did not observe significant differences between the two groups six weeks postoperatively. We have observed greater axon diameter, with greater thickness of the myelin sheath and better epineurial and perineurial organization in the VNG after 30 and 90 days.…”
Section: Discussionmentioning
confidence: 91%
“…脙 p < 0.05. effective vascularized nerve grafting over a period of 1 to 24 weeks using nerves such as sciatic nerve. [6][7][8] For elucidating the efficacy of vascularized nerve grafting over an extended period, this study performed a histological and physiological evaluations over a period of 30 weeks, which was much longer than the periods investigated in previous studies. Using the vascularized median nerve model, this study successfully showed that vascularized autologous nerve grafts provided better outcome in several nerve-regeneration parameters than in nonvascularized grafts for repairing facial nerve deficits.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, the histological and physiological basis of the therapeutic efficacy of the vascularized autologous nerve graft in facial nerve regeneration remains poorly understood, because in part no established rat model with vascularized autologous nerve grafts for facial nerve regeneration is available. Although rat experimental models having sciatic and femoral nerve defects have been well used by many researchers for vascularized nerve studies, [6][7][8] no facial nerve reconstruction model with a vascularized nerve is developed because of its complicated anatomy.…”
mentioning
confidence: 99%
“…17 Quantification of ChAT has been reported as a way of determining not only motor neuron function, but also possibly assisting in the differentiation between motor and sensory fibers as well as continuity of the nerve root. 1,11 The potential of using ChAT quantification for clinical use has been reported in the last 2 decades. 3,4 Hattori et al [7][8][9] reported that the level of ChAT activity could be used as a reliable indication of motor fascicles, based on a few clinical cases with intraoperative ChAT assays.…”
Section: 漏Aans 2014mentioning
confidence: 99%